Offshore oil and gas development legal framework - Vann, Adam. (UK Congressional Research, 2010)
The development of offshore oil, gas, and other mineral resources in the United States is impacted by a number of interrelated legal regimes, including international, federal, and state laws. International law provides a framework for establishing national ownership or control of offshore areas, and domestic federal law mirrors and supplements these standards.
Keywords: Oil and Gas